Islamic fashion and anti-fashion new perspectives from Europe and North America - Tarlo, Emma; Moors, Annelies 1953- (Bloomsbury Academic, 2013)
Introducing innovative new research from international scholars working on Islamic fashion and its critics, Islamic Fashion and Anti-Fashion provides a global perspective on muslim dress practices. The book takes a broad geographic sweep, bringing together the sartorial experiences of Muslims in locattions as diverse as Paris, the Canadian Prairie, Swedish and Italian bath houses and former socialist countries of Eastern Europe. What new Islamic dress practices and anxieties are emerging in these different locattions? How far are they shaped by local circumstances, migration histories, particular religious traditions, multicultural interfaces and transnational links? To what extent do developments in and debates about Islamic dress cut across such local specificities, encouraging new channels of communication and exchange? With original contributions from the fields of anthropology, fashion studies, media studies, religious studies, history, geography and cultural studies, Islamic Fashion and Anti-Fashion will be of interest to students and scholars working in these fields as well as to general readers interested in the public presence of Islam in Europe and America
Keywords: Islamic clothing and dress -- Europe; Islamic clothing and dress -- America; Mode; Muslimin; Nordamerika; Europa; Türkei; Aufsatzsammlung